Predicting the electromechanical properties of small caliber projectile impact igniter using PZT dynamic damage constitutive model considering crack propagation - Rui-zhi Wang; Zhi-qiang Wang; En-ling Tang; Lei Li; Guo-lai Yang; Chun Cheng; Li-ping He; Ya-fei Han (Defence Technology, 2023)
Block piezoelectric ceramics (PZTs) are often used in impact igniters to provide activation energy for electric initiators. Under the action of strong impact stress, PZTs release electric energy accompanied by crack initiation, propagation and crushing. At present, the electrical output performance of PZTs in projectile is usually calculated by quasi-static piezoelectric equation without considering the dynamic effect caused by strong impact and the influence of crack propagation on material properties. So the ignition parameters are always not accurately predicted. To tackle this, a PZT dynamic damage constitutive model considering crack propagation is established based on the dynamic impact test and the crack propagation theory of brittle materials. The model is then embedded into the ABAQUS subroutine and used to simulate the electromechanical response of the impact igniter during the impact of a small caliber projectile on the target. Meanwhile, the experiments of projectile with impact igniter impact on the target are carried out. The comparison between experimental and numerical simulation results show that the established dynamic damage model can effectively predict the dynamic electromechanical response of PZTs in the missile service environment.